THE EFFECT OF CITOCININE CONCENTRATION ON THE GROWTH OF PINEAPPLE LEAF CUTTINGS - etriadi, etriadi; Warganda, Warganda; Listiawati, Agustina (Jurnal Sains Mahasiswa Pertanian, 2019)
Plant Growth Regulator (PGR) are non-nutrient organic compounds, which in small amounts can support, inhibit and can change the physiological processes of plants. On the PGR bosa used to stimulate shoot growth in pineapple leaf cutting is benzyl adeno purine (BAP) from the cytokines group. This study aims to find the concentration of cytokines for the growth of pineapple leaf cuttings. The design used in this study was a Completely Randomized Design (CRD) with 6 levels of Cytokinin treatment and each treatment had 4 replications, each replication had 5 samples, so there were 6 x 4 x 5 = 120 units of experiment. The treatment of cytokines consists of: s0 = without the administration of cytokines, s1 = 0.2 mg / l, s2 = 0.3 mg / l, s3 = 0.4 mg / l, s4 = 0.5 mg / l, s5 = 0.6 mg / l. The variables observed in this study were the time of formation of shoots (days), the percentage of shoot formation (%), shoot height (cm), number of shoots (shoots), number of leaves (strands). The results showed that the various cytokines concentration had non significant effect on the time of bud formation, shoot height, number of shoots and number of leaves.Â